Tingkat Kepuasan Konsumen terhadap Pelayanan Kefarmasian di Apotek Ganesha Farma Kabupaten Lamongan - Nisa', Zahrotun; Sugihantoro, Hajar; Syahrir, Ach; Wijaya, Dhani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Pharmaceutical service is a form of health service in pharmacy as an inseparable unit that plays a significant role in improving the quality of life of patients and also increasing patient satisfaction. Based on the preliminary study, the services whose provided by the Ganesha Farma Pharmacy staff are less satisfying to consumers, related to the friendliness of the pharmacy staff and the lack of provision of drug information by pharmacy staff. Therefore, in this study, it is expected to know the level of customer satisfaction at the Ganesha Farma Pharmacy, Lamongan Regency. The purpose of this study was to determine the level of customer satisfaction with pharmaceutical service at Ganesha Farma Pharmacy in Lamongan Regency. The type of research was descriptive with a quantitative approach. The sampling method was non-probability sampling with the purposive sampling technique. The samples obtained were 100 respondents. The method of calculating the level of customer satisfaction was the Customer Satisfaction Index (CSI) method. The results showed that the level of satisfaction at the reliability dimension of 70.8% (satisfied), responsivenesss 68.8% (satisfied), assurance 69% (satisfied), empathy 69.8 (satisfied), tangible 69.4% (satisfied). The conclusion of this study is the level of customer satisfaction towards pharmaceutical services at Ganesha Farma Pharmacy, Lamongan Regency is 69.56% with the satisfied category.Keywords: Level of customer satisfaction, Pharmacy, Pharmaceutical services